Incidence of tenosynovitis or peritendinitis and epicondylitis in a meat-processing factory. - Kurppa, Kari; Viikari-Juntura, Eira; Kuosma, Eeva; Huuskonen, Matti; Kivi, P. (Scandinavian Journal of Work, Environment & Health, 1991)
A 31-month follow-up study on the incidence of clinically ascertained tenosynovitis or peritendinitis in the hand and forearm regions and epicondylitis was conducted among 377 workers in strenuous manual jobs and 338 employees in manually nonstrenuous work in a large meat-processing factory. The clinical diagnosis of tenosynovitis or peritendinitis occurred 143 times and epicondylitis 68 times during the follow-up. The annual incidence of tenosynovitis or peritendinitis was less than 1% for employees in nonstrenuous jobs, 25.3% for female packers, 16.8% for female sausage makers, and 12.5% for male meatcutters. The annual incidence of epicondylitis was about 1% for employees in nonstrenuous jobs, 11.3% for female sausage markers, 7.0% for female packers, and 6.4% for male meatcutters. Workers typically resumed their jobs after returning from sick leave, and job transfers were rare.